2014
DOI: 10.1073/pnas.1402588111
|View full text |Cite
|
Sign up to set email alerts
|

Differential targeting of VDAC3 mRNA isoforms influences mitochondria morphology

Abstract: Intracellular targeting of mRNAs has recently emerged as a prevalent mechanism to control protein localization. For mitochondria, a cotranslational model of protein import is now proposed in parallel to the conventional posttranslational model, and mitochondrial targeting of mRNAs has been demonstrated in various organisms. Voltage-dependent anion channels (VDACs) are the most abundant proteins in the outer mitochondrial membrane and the major transport pathway for numerous metabolites. Four nucleus-encoded VD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 42 publications
3
52
0
Order By: Relevance
“…Indeed, our group has thus far failed, after many attempts, to express and import CYB into the mitochondria (data not shown). We hope, however, that with careful experimentation and additional levels of targeting (such as RNA targeting to promote co-translational import) (5,62), that this approach will someday become generalized to any of the 13 proteins of the mitochondrial genome.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our group has thus far failed, after many attempts, to express and import CYB into the mitochondria (data not shown). We hope, however, that with careful experimentation and additional levels of targeting (such as RNA targeting to promote co-translational import) (5,62), that this approach will someday become generalized to any of the 13 proteins of the mitochondrial genome.…”
Section: Discussionmentioning
confidence: 99%
“…79 More recently, cellular fractionations and in vivo imaging using the MS2-tagging system revealed that VDAC3 mRNAs are associated with mitochondria in Arabidopsis thaliana. 80 Interestingly, VDAC3 transcripts that varied in their 3 0 -UTR length differed in their association, and a region of 140 nts from the 3 0 -UTR appeared sufficient to induce localization of a heterologous mRNA to the mitochondria. These results indicate that localization of VDAC3 mRNA can occur in a non-translational manner, via cis elements from the 3 0 -UTR.…”
Section: Conservation Among Speciesmentioning
confidence: 97%
“…30,44 Studies from numerous taxa have demonstrated the importance of localized translation to mitochondrial activity. In Arabadopsis thaliana, interference with the localization of mRNA of the membrane protein VDAC3 affected mitochondrial morphology and size 80 and in yeast, the correct localization of ATP2 mRNA was shown to be important for respiration. 41 In human fibroblasts, induced localization of ATP6 mRNA to the mitochondrial outer membrane resulted in the rescue of mitochondrial defects.…”
Section: Functional Relevancementioning
confidence: 99%
“…In yeast, the mRNAs of Tom40, Tob55 and the two isoforms of Porin showed little or no mitochondrial localization, while the mRNA of another β‐barrel protein, mitochondrial distribution and morphology 10 (Mdm10) seemed to be partially enriched in the vicinity of mitochondria . In plant cells, mRNA encoding the β‐barrel protein VDAC3 was shown to be associated with mitochondria . However, while a cotranslational import leads to an mRNA localization to the site of import, the reverse is not necessarily true.…”
Section: Import Mode: Is It Co‐ or Posttranslational?mentioning
confidence: 99%
“…However, while a cotranslational import leads to an mRNA localization to the site of import, the reverse is not necessarily true. In fact, targeting of VDAC3 mRNA to mitochondria is not required for an efficient import of the protein .…”
Section: Import Mode: Is It Co‐ or Posttranslational?mentioning
confidence: 99%